APPLICATION OF HYBRID SYSTEM OF ENERGY SOURCES IN TEMPE FERMENTATION DEVICE - Yulita Dwi Setyaningsih , Noor; Bagus, Mochammad Bagus Putro Wibowo (Jurnal Media Elektrik, 2025)
Tempeh fermentation tool designed with a hybrid system that combines PLN electricity and solar panels successfully optimizes energy use with a relatively low sensor error value, an average of less than 10%. This system is able to switch energy sources from solar panels to PLN electricity automatically based on the measured voltage, thus minimizing the risk of fermentation process failure. Testing of electricity consumption shows a consistent increase in consumption per hour, with a total power consumption of 1,997 kWh for 22 hours when using PLN electricity. This shows the efficiency and reliability of the tool in supporting the tempeh fermentation process in a more controlled and energy-efficient manner.